Dyeing of a Blended Fabric with a Continuous Method with Active and Dispersive Dye - M. B. Irmatova; I. A. Nabiyeva; N. M. Sharipova (Researchparks Publishing, 2022)
In the article the possibilities of obtaining intense and uniformly colors for dyeing blended fabrics on basis of cotton and polyester fibers of various proportions with the use of a combination of active and disperse dyes and studies. The color indices of the samples stained according to the proposed technology are given.